The effects of biochars on the growth of Zelkova serrata seedlings in a containerized seedling production system. Issue 1 (2nd January 2017) - Cho, Min Seok; Meng, Loth; Song, Ji-Hye; Han, Si Ho; Bae, Kikang; Park, Byung Bae
ABSTRACT: Biochar has been used for soil improvement in agriculture; however, there are few studies of its uses in forestry. The purpose of this study was to investigate the effects of biochar, made from diverse feedstocks on the growth and chlorophyll content of Zelkova serrata seedlings, to identify optimal feedstocks in a containerized seedling production. Five resources were used for biochar: woodchips of Pinus densiflora and Quercus acutissima ; cones of Pinus koraiensis ; rice husks; and crab shells. The biochar was mixed with growing medium by 20% in volume and two levels of fertilization were applied. The height and root collar diameter of Z. serrata treated with wood chips of P. densiflora and Q. acutissima and rice husk were each significantly greater than those treated with pine cones and crab shells. The biomass responses and quality indexes were similar to those of height and root collar diameter. There were no significant differences in growth between fertilization levels. This study shows that biochar made from woodchips of P. densiflora and Q. acutissima and rice husk can be substituted for growing medium by 20% in a containerized seedling production system.